We must not despair in our search for goodness - Abd Razak, Dzulkifli (2008)
DEEPAVALI, or Divali, which literally means "a row of lamps", is commonly known as the "festival of lights". It is one of the most prominent festivals of the Indian community. It signifies the day when darkness and ignorance gave way to light and knowledge, and death to eternal life. This is symbolically expressed by the lighting of lamps using natural oil, such as coconut oil. The festival is celebrated over four to six days on the dark fortnight of the Hindu month of Ashwin (or Aasho) which usually falls in the month of October or November, depending on the lunar calendar.